2018
DOI: 10.1159/000487439
|View full text |Cite
|
Sign up to set email alerts
|

Challenges in Infectious Diseases for Haematologists

Abstract: Infections remain a threat for patients with haematological malignancies. In accordance with the European Hematology Association roadmap we provide a concise overview regarding the most relevant current challenges in infectious diseases for haematologists. These include bacterial infections and the need for antibiotic stewardship as well as infections with community-acquired respiratory viruses, infections in patients receiving targeted therapies, re-activations of latent infections and vaccination strategies.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…sepsis). In such cases, it can be crucial for the spectrum of efficacy of empirical antibiotic treatment to include pathogens with specific resistance [ 142 ], [ 143 ], [ 144 ], [ 148 ], [ 342 ], [ 346 ], [ 347 ], [ 348 ], [ 349 ], [ 350 ], [ 351 ], [ 361 ], [ 362 ], [ 388 ], [ 389 ], [ 390 ], [ 391 ], [ 392 ], [ 393 ], [ 394 ], [ 395 ], [ 396 ], [ 397 ], [ 398 ], [ 399 ], [ 400 ], [ 401 ], [ 402 ], [ 403 ], [ 404 ], [ 405 ], [ 406 ], [ 407 ], [ 408 ], [ 409 ], [ 410 ], [ 411 ], [ 412 ], [ 413 ], [ 414 ]. On the other hand, this must not lead to prolonged uncritical use of reserve antibiotics [ 156 ], [ 415 ], [ 416 ], [ 417 ], [ 418 ], [ 419 ], [ 420 ], [ 421 ].…”
Section: Recommendationsmentioning
confidence: 99%
See 1 more Smart Citation
“…sepsis). In such cases, it can be crucial for the spectrum of efficacy of empirical antibiotic treatment to include pathogens with specific resistance [ 142 ], [ 143 ], [ 144 ], [ 148 ], [ 342 ], [ 346 ], [ 347 ], [ 348 ], [ 349 ], [ 350 ], [ 351 ], [ 361 ], [ 362 ], [ 388 ], [ 389 ], [ 390 ], [ 391 ], [ 392 ], [ 393 ], [ 394 ], [ 395 ], [ 396 ], [ 397 ], [ 398 ], [ 399 ], [ 400 ], [ 401 ], [ 402 ], [ 403 ], [ 404 ], [ 405 ], [ 406 ], [ 407 ], [ 408 ], [ 409 ], [ 410 ], [ 411 ], [ 412 ], [ 413 ], [ 414 ]. On the other hand, this must not lead to prolonged uncritical use of reserve antibiotics [ 156 ], [ 415 ], [ 416 ], [ 417 ], [ 418 ], [ 419 ], [ 420 ], [ 421 ].…”
Section: Recommendationsmentioning
confidence: 99%
“… That the medical professional associations in the AWMF continue with the progressive development and detailed formulation of existing guidelines on antimicrobial stewardship [ 381 ], [ 382 ] for the different clinical areas in which immunosuppressed patients are treated so that the characteristics of this patient population are given proper consideration [ 148 ], [ 270 ], [ 351 ], [ 408 ], [ 447 ], [ 448 ], [ 449 ], [ 450 ], [ 451 ], [ 452 ], [ 453 ], [ 454 ], [ 455 ], [ 456 ], [ 457 ], [ 458 ], [ 459 ], [ 460 ], [ 461 ], [ 462 ], [ 463 ], [ 464 ], [ 465 ], [ 466 ] (cat. II).…”
Section: Recommendationsmentioning
confidence: 99%
“…Despite the lack of data currently available on COVID-19 outcomes in patients with hematologic diseases, a nationwide case analysis from 575 hospitals in China suggested that, in general, immunosuppressive patients were more likely to contract COVID-19 and, most importantly, there was a higher risk of severe events among those patients, including admission to ICUs, need for assisted ventilation and number of death cases [4]. In the spring of 2020, the European Hematology Association presented several issues that challenge the managing of hematologic patients due to a changed work environment, personnel sicknesses, shortages of blood products and patients not receiving adequate therapy within the required time frame in an emergency setting [17]. The EHA experts also suggested that despite the absence of specific data, potential risk factors for severe courses of SARS-CoV-2 infection can be severe immunodeficiency, lymphopenia and long and profound neutropenia.…”
Section: Hematologic Diseases and Covid-19mentioning
confidence: 99%
“…As a hematologist with an interest in infectious diseases I would like to use this opportunity to repeat a long-standing message: community-acquired respiratory viruses (CARV) are potential killers, especially for cancer patients [1]. Influenza has long been famous for causing seasonal excess mortality in all populations and is therefore well known as a dangerous pathogen in cancer patients in particular [2, 3].…”
mentioning
confidence: 99%